The comparison of perceptions of the economic impact of COVID-19 and the 2015 Ranau earthquake among homestay entrepreneurs in Kundasang, Sabah Kundasang, Sabah - Roslinah Mahmud; Khairul Hanim Pazim @ Fadzim; Lim, Beatrice Fui Yee; Kasim Md. Mansur; Borhan Abdullah; Rostika Petrus Boroh (Human Resource Management Academic Research Society (HRMARS), 2022)
The COVID-19 pandemic, which has been affecting Malaysia since January 2020, has had a substantial impact on the country's tourism industry. The pandemic compelled Malaysia's government to enact the Movement Control Order (MCO) in March 2020 in order to halt the spread of the virus. The MCO is still being implemented with a sequence of MCO 1.0, MCO 2.0, and MCO 3.0. The MCO has a significant impact on Sabah, particularly on the tourism industry, which is the state's primary source of revenue. The Kundasang district in Sabah has also faced several economic issues, particularly among homestay entrepreneurs. Not only COVID-19 in 2020 but also the earthquake disaster that occurred in June 2015, had a significant impact on the operations and profits of these homestay entrepreneurs. The purpose of this study is to examine descriptively the perspective of the economic consequences of the COVID-19 pandemic and the Ranau 2015 earthquake catastrophe among homestay entrepreneurs in Sabah, particularly in Kundasang Sabah. Homestay is one of the tourism activities in Kundasang that makes extensive use of Community-Based Tourism (CBT). A structured questionnaire was distributed to homestay entrepreneurs in Kundasang, Sabah, as part of the research process. Kundasang, which is well-known in Sabah, provides highland landscape tourism, which has resulted in numerous homestay businesses that generate income for the locals. According to the findings of this study, the influence of COVID-19 and the Ranau 2015 earthquake catastrophe had a similar effect in terms of income on homestay entrepreneurs in Kundasang Sabah.